Implementasi Algoritma Code-Excited Linear Prediction (Celp) Pada Kompresi File Audio - Lucius Yupiter Telaumbanua; Efori Bu’ulolo; Kurnia Ulfa (STMIK Budi Darma, 2022)
The use of storage media to store various files, whether text, video or audio, has been implemented for a long time and continues to grow today. The size of a file will affect the data transmission process as well as the use of large enough storage space. This is what lies behind the application of the compression process to a file so that the file size can be reduced and simplify the process of data transmission and use less storage space. One file that is often compressed is an audio file. Audio files often use a large enough storage space when compared to other document files. This is why compression of audio files is needed. In compressing audio files, the author will use the CELP method. This method is part of lossy compression. The lossy compression method recognizes that human hearing is limited so that not all data in the audio file can be heard directly. The lossy algorithm will provide a fairly large change in file size compared to lossless compression. The CELP method is applied because it can perform coding efficiently and the quality is maintained. In this study, it is known that the application of the CELP method on audio files produces an audio file compression application, especially those with the Mp3 extension. The compressed Mp3 audio file has a very small size with a compression ratio of 7.38%.